MY LAW AND MODERNIZATION JOURNEY - Souza Santos, Boaventura de (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2021)
History is always written backwards, from the present to the past. Most of the time, this sequence remains hidden in the historical narrative of any given existential experience. In this chapter, I will start by analyzing how I see, today and in retrospect, the historical and political context of the Law and Modernization Program [L&MP]. I will then move to analyze my journey at Yale University in the early 1970s. It will be evident how the turbulence and the excitement of the latter analysis reproduces in a foggy and messy way the greater clarity and assertiveness of the first analysis. Social and political history has a double existence: as macro-history of the large-scale societal forces that shape the social and political processes at national and transnational levels; and as micro-history of individuals and communities as they express their creativity within such processes, managing resources and resistances, opportunities and constraints, often partly or totally unaware of the macro-history of which they are part. The two levels of history do intersect and influence each other in unfathomable ways, but each one has its own dynamic and neither level in isolation can tell the whole story of history. <a title="" href="https://d.docs.live.net/a4fa3b7694794c6e/REVISTA%20ESTUDOS%20INSTITUCIONAIS/Vol7%20Num2/Artigos%20Internacionais/5.%20My%20Law%20and%20Modernization%20Journey%20(de%20Sousa%20Santos).docx#_ftn1">[1] I will conceive the personal journey of the different participants in the L&MP as micro-history, and so as inserted in specific ways in a macro-history, the post-World War II period, Cold War and US international politics, particularly concerning its historically privileged region of influence, Latin America. Even though I will mainly focus on the micro-level history, in the first section I will briefly mention the main facets of the macro-history as I understand it.